2014
DOI: 10.1007/s00223-014-9859-2
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in Perlecan/HSPG2 During Bone Development Enhances Osteogenesis and Decreases Quality of Adult Bone in Mice

Abstract: Perlecan/Hspg2 (Pln) is a large heparan sulfate proteoglycan abundant in the extracellular matrix of cartilage and the lacuno-canalicular space of adult bones. While Pln function during cartilage development is critical, evidenced by deficiency disorders including Schwartz-Jampel Syndrome and dyssegmental dysplasia Silverman-Handmaker type, little is known about its function in development of bone shape and quality. The purpose of this study was to understand the contribution of Pln to bone geometric and mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
1
28
2
Order By: Relevance
“…1). Homozygous animals showed low levels of perlecan that appeared to be restricted to the intracellular compartment, which is consistent with a previous report that showed that perlecan in (Neo/Neo) mice is sequestered in the endoplasmic reticulum and is likely degraded (Lowe et al, 2014). In heterozygous and wild-type E16.5 embryos, perlecan was found throughout the distal humerus, (Fig.…”
Section: Resultssupporting
confidence: 92%
“…1). Homozygous animals showed low levels of perlecan that appeared to be restricted to the intracellular compartment, which is consistent with a previous report that showed that perlecan in (Neo/Neo) mice is sequestered in the endoplasmic reticulum and is likely degraded (Lowe et al, 2014). In heterozygous and wild-type E16.5 embryos, perlecan was found throughout the distal humerus, (Fig.…”
Section: Resultssupporting
confidence: 92%
“…A report concluded that there are 15 members in the HSPGs. Among these members, Sdc2 and HSPG2 have been suggested to be involved in skeleton formation (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Sdc2 is abundant in putative precursor cells of hard and connective tissue, and its expression is high in prechondrogenic cells, decreases in differentiating chondrocytes, and persists in the perichondrium and periosteum at the onset of osteogenesis (42). HSPG2 is abundant in the extracellular matrix of cartilage and the lacunocanalicular space of adult bones, and deficiency in HSPG2 during bone development enhances osteogenesis and decreases quality of adult bone in mice (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the disorganization of the growth plate and chondro-osseous junction of bones caused by the absence of perlecan, there are other distortions in the growth of joints including the temporo-mandibular joint, myotonia and electrical disturbances of muscle and modifications to the structures of facial bones (30). Moreover, perlecan deficiency in hypomorphic mutant mice influences bone formation by enhancing osteogenesis and concurrently affects mineralization, leading to increased brittleness at older ages (31). …”
Section: Perlecan Geneticsmentioning
confidence: 99%